Risk factors for motor decline following parasagittal and falx meningioma resection in the middle third - Guo, Chengxuan; Xue, Yafei; Li, Yang; Tian, Qilong; Qu, Yan; Cai, Qing (Frontiers in Oncology, 2025)
ObjectiveThe resection of parasagittal and falx meningiomas in the middle third superior sagittal sinus (SSS) is associated with a high risk of postoperative motor deficits. This study discusses the risk factors affecting postoperative motor decline and recovery of motor function after follow-up.MethodsThe results of a single-institution retrospective cohort study of parasagittal and falx meningioma resection in the middle third between 2016 and 2023 were reviewed, and parameters were screened as potential predictors. Variables of interest included postoperative motor decline and outcome after follow-up. Univariate and multivariate analyses were performed to identify risk factors.ResultsAmong 87 patients who underwent resection of parasagittal (63.2%) or falx (36.8%) middle third meningiomas, 14.9% (13/87) experienced postoperative motor decline. Among the 36 patients (41.4%) with preoperative motor deficits, 66.3% improved, 17.0% unchanged, and 16.7% (6/36) worsened following surgery. Among the 51 patients without preoperative motor deficits, 13.7% (7/51) developed new weakness. The predictors of postoperative motor decline were major venous involvement (p = 0.022), falx meningioma (p = 0.031), loss of the brain-tumor interface (p=0.033) and WHO grade II-III (p = 0.032).ConclusionsThe resection of parasagittal and falx meningiomas in the middle third carries a high rate of postoperative morbidity and deserves perioperative planning. Alternative surgical strategies, such as preserving the brain-tumor arachnoid interface and minority residual tumors, may prevent motor decline in a subset of high-risk patients.